Progress in cryptology -- INDOCRYPT 2014 : 15th International Conference on Cryptology in India, New Delhi, India, December 14-17, 2014, Proceedings - Mukhopadhyay, Debdeep; Meier, Willi (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 15th International Conference on Cryptology in India, INDOCRYPT 2014, held in New Delhi, India, in December 2014.   The 25 revised full papers presented together with 4 invited papers were carefully reviewed and selected from 101 submissions. The papers are organized in topical sections on side channel analysis; theory; block ciphers; cryptanalysis; efficient hardware design; protected hardware design; elliptic curves.